Comparison of Regulations Concerning Protection of Migrant Workers Between Indonesia and the Philippines - David Leonardo (Dinasti Research, 2024)
Many Indonesian citizens decide to become migrant workers abroad due to the lack of opportunities to work in the country. But unfortunately, while working abroad, many Indonesia migrant workers receive inappropriate treatment from their employers, such as being mistreated or having their documents confiscated. Taking into account these conditions, the Indonesia government promulgated Law Number 18 of 2017 concerning the Protection of Indonesia Migrant Workers. This study aims to identify the similarities and differences in the legal policies of the two countries, as well as analyze how these regulations are applied in protecting the rights of migrant workers. This study uses a comparative law method, where Indonesia law will be used as the main reference (primum comparandum), while Philippine law will be used as a comparison (secundum comparatum). The results show that Indonesia has several regulations to protect migrant workers, but they are not yet fully effective, especially compared to the more systematic Philippine law in certain aspects, such as lending and legal aid services for migrant workers. Although Indonesia's laws are more detailed, the regulations are still not comprehensive, so it is necessary to pay attention to the advantages of Philippine law to increase protection for Indonesia's migrant workers in the future.